2017
DOI: 10.1080/20008198.2017.1421819
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of ICD-11 adjustment disorder research

Abstract: Background: Adjustment disorder (AjD) is one of the most used mental disorder diagnoses among mental health professionals. Important revisions of the AjD definition in the 11th edition of the International Classification of Diseases (ICD-11) are proposed. AjD is included in a chapter of disorders specifically associated with stress in ICD-11. Objective: This paper aims to review recent developments in ICD-11 AjD research, and to discuss the available ICD-11 AjD diagnosis validation studies, AjD measures, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…Previous studies supported the factor structure of the brief 8-item ADNM-8 measure (Kazlauskas, Zelviene, Lorenz, et al, 2017), and good psychometric characteristics of the ADNM-8 were reported in several studies (Ben-Ezra et al, 2018;Kazlauskas et al, 2018;Lorenz et al, 2018a;Zelviene et al, 2017). In this study, Cronbach's α was .89 for the total ADNM-8 scale, α = .87 was for the ADNM-8 preoccupation subscale, and α = .79 for the ADNM-8 failure to adapt subscale.…”
Section: Adjustment Disorder Symptomssupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies supported the factor structure of the brief 8-item ADNM-8 measure (Kazlauskas, Zelviene, Lorenz, et al, 2017), and good psychometric characteristics of the ADNM-8 were reported in several studies (Ben-Ezra et al, 2018;Kazlauskas et al, 2018;Lorenz et al, 2018a;Zelviene et al, 2017). In this study, Cronbach's α was .89 for the total ADNM-8 scale, α = .87 was for the ADNM-8 preoccupation subscale, and α = .79 for the ADNM-8 failure to adapt subscale.…”
Section: Adjustment Disorder Symptomssupporting
confidence: 78%
“…It has also been stated that the definition of ICD-10 adjustment disorder was often used as a provisional or residual diagnostic category when the reactions did not fully represent other mental disorders (Maercker et al, 2013). Therefore, new studies, testing the symptom profile of ICD-11 adjustment disorder, its prevalence, and risk factors have emerged following ICD-11 proposals for a new definition (Kazlauskas, Zelviene, Lorenz, Quero, & Maercker, 2017;Maercker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kazlauskas et al reviewed more recent developments in ICD‐11 AjD research relating and noted that all studies used the ‘Adjustment Disorder New Module’ (ADNM) to measure ICD‐11 AjD. The ADNM is a self‐report measure developed prior to the formulation of the ICD‐11 narrative description for AjD.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…Kazlaukas, Zelviene, Lorenz, Quero, and Maercker (2017) provide a scoping literature review on studies of the proposed revised ICD-11 conceptualization of adjustment disorder (AjD), including a brief overview of the historical background, AjD measurements, and the treatment studies. The review identifies 10 studies, which are focused on measurement validation, the latent structure of AjD, predictors of AjD, and/or treatment of AjD.…”
Section: Childhood Maltreatmentmentioning
confidence: 99%